Framework for technical communication skills content development for students in Malaysian Vocational Colleges: a fuzzy delphi study - Jamaludin, Khairul Azhar; Alias, Norlidah; DeWitt, Dorothy; Abdul Razzaq, Abdul Rasid (Penerbit UTHM, 2019)
Developing technical communication is vital to ensure employability of graduates in Technical and Vocational Education and Training (TVET) institutions. However, limited studies are available to guide its development in Malaysian Vocational Colleges. Hence, this study is aimed at proposing a framework for technical communication development for effective implementation in Malaysian Vocational Colleges. This study employs Fuzzy Delphi Method (FDM) with 17 experts from industry and TVET institutions in identifying the prominent content of learning for technical communication skills development of students in Malaysian Vocational Colleges. Generally, the findings suggest that all clusters of technical communication skills (oral technical, written technical, interpersonal and researching skills) are important to be emphasised as the content of learning, with a high percentage of agreement (>75%). However, a number of items under Content of Learning components were omitted. For instance, two items under Oral Technical Communication, eight items under Written Technical Communication, two items under Interpersonal and one item under Researching Skills achieved percentage of agreement below 75%. The proposed framework is a relevant reference in introducing technical communication in Malaysian Vocational Colleges.